Perancangan PLTS pada Smart Greenhouse di Lahan Pertanian Wijaya Farm, Lembang, Bandung: Design of Off-grid Solar Power System for Smart Greenhouse at Wijaya Farm Agricultural Land, Lembang, Bandung - Simorangkir, Arthur; Halim, Levin; Arthaya, Bagus (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The problem of limited access to electricity in the agricultural sector will have a direct impact on the suboptimal operation of smart greenhouses, including irrigation systems, additional lighting, and sensor-based environmental monitoring. The absence of a reliable energy source makes it difficult for farmers to maintain the stability of the planting environment, especially in remote areas that are not covered by the PLN electricity network. This community service activity aims to design an off-grid Solar Power Plant (PLTS) system as an independent energy solution that is efficient, environmentally friendly, and accessible to farmers in the location. The methods used include direct surveys to obtain data on electricity load requirements, measuring location conditions to determine orientation and potential for solar radiation, and technical calculations of the system based on field data. The result of this activity is a PLTS system design with a 2320 Wp solar panel configuration, 3 kW inverter, and 48V 150Ah battery, which is projected to be able to meet the daily energy needs of 2880 Wh and can maintain greenhouse operations for two days without sunlight. This activity also provides benefits in increasing farmer literacy regarding solar energy technology and encouraging initiatives to implement similar off-grid PLTS systems independently. This community service activity shows that the design of an off-grid PLTS system based on actual needs has great potential to be replicated as a sustainable energy solution in the agricultural sector.